ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU TEPUNG TERIGU DENGAN METODE EOQ (Economic Order Quantity): Studi Kasus di Qini Bakery Idrisiyyah Rajapolah - Ahmad Munsyi Muttaqi; Budhi Wahyu Fitriadi; Rita Tri Yusnita (Melati Institute, 2022)
This study aims to determine how the effect of using the EOQ method on Qini Bakery Idrisiyyah Rajapolah and is there any difference between Qini Bakery Idrisiyyah Rajapolah before and after using the EOQ method. The main raw materials used in Qini Bakery Idrisiyyah Rajapolah is Coconut Shell. Qini Bakery Idrisiyyah Rajapolah processes the shell into Briquettes. This study uses interview data collection techniques, library research, and observation. The method used in this study is a qualitative descriptive method. The data analysis method used is Economic Order Quantity (EOQ), Safety Stock, Reorder Point and Total Inventory Cost. Based on the results of the study that by calculating the Economic Order Quantity (EOQ) method the company can optimize inventory and can streamline inventory costs.